Documentation and diagnosis of delirium in Parkinson's disease. (19th July 2022) - Cullinan, Rachel J.; Richardson, Sarah J.; Yarnall, Alison J.; Burn, David J.; Allan, Louise M.; Lawson, Rachael A.
Abstract: Objective: To assess the accuracy of documentation of the symptoms and diagnosis of delirium in medical notes of inpatients with Parkinson's disease (PD). Methods: The DETERMINE‐PD pilot study assessed PD inpatients over 4‐months. Delirium prevalence was classified prospectively using a standardized assessment at a single visit on the basis of Diagnostic and Statistical Manual of Mental Disorders 5th Edition (DSM‐5) criteria. Incident delirium was diagnosed retrospectively using detailed clinical vignettes and validated consensus method. Inpatient medical notes and discharge summaries of those with delirium were reviewed for documentation of symptoms, diagnosis and follow‐up. Results: Forty‐four PD patients consented to take part in the study, accounting for 53 admissions. We identified 30 cases (56.6%) of delirium during the participants' stay in hospital. Of those with delirium identified by the research team, delirium symptoms were documented in the clinical notes of 72.3%; 37.9% had a delirium diagnosis documented. Older patients were more likely to have delirium ( p  = 0.027) and have this diagnosis documented ( p  = 0.034). Time from documentation of symptoms to diagnosis ranged from <24 h to 7 days (mean 1.6 ± 4.4 days). Hypoactive delirium was significantly less likely to have been identified and formally diagnosed (63% of not documented were hypoactive vs. 37% hyperactive, mixed or unclear, p  = 0.016). Only 11.5% of discharge summaries included diagnosis of delirium. Conclusion: Delirium in PD is common. Documentation of symptoms of delirium was common; however, fails to lead to a documentation of diagnosis in over half of admissions with delirium and was even less commonly communicated in the Primary Care discharge summaries. This highlights the need for increased education about delirium symptomatology and diagnosis in PD.